Solvent-free electrode

By developing solvent-free electrodes in lithium-ion battery packs, the safety and leakage problems of traditional liquid electrolytes are solved by using the combination of active materials, carbon-based materials and specific polymers, and the life and performance of the battery pack are improved through tight interfaces.

CN119764447APending Publication Date: 2025-04-04THE SWATCH GRP RES & DEVELONMENT LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411396512.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-10-03
Filing Date
2024-10-08
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The liquid electrolytes in traditional lithium-ion battery packs have high safety and leakage risks, and the solid electrolyte is insufficient in the interface between the electrode and the electrolyte, resulting in a shortening of the battery pack life.

Method used

A solvent-free electrode is developed, including an active material, a carbon-based material and a polymer having a maleimide group, an acrylate group or a methacrylate group as a binder, and the electrode is manufactured by hot pressing to form a close interface with the solid electrolyte.

Benefits of technology

The high mechanical strength and high energy density of solvent-free electrodes are achieved, which extends the life of the battery pack, improves the performance of the battery, simplifies the manufacturing process, and reduces production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119764447A_ABST
    Figure CN119764447A_ABST
Patent Text Reader

Abstract

The invention relates to a solvent-free electrode (2, 3) for a lithium-ion battery (1), comprising:-an active material as a source of lithium ions capable of receiving lithium ions and / or releasing lithium ions into its structure; -a carbon-based material to increase the conductivity of the electrode; characterised in that it further comprises a polymer having at least a maleimide group, an acrylate group or a methacrylate group, said polymer acting as a binder between the active material and the carbon-based material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a solvent-free electrode and a method for manufacturing the same, and also to a battery comprising the solvent-free electrode and an optional solid electrolyte. Technical Background

[0002] Conventional batteries, such as lithium-ion (Li-ion) batteries, containing liquid electrolytes have been known for decades. However, it is well known that these liquid electrolytes can adversely affect the safety of the battery, for example, due to the generation of lithium metal dendrites, which can cause the battery to short-circuit. In addition, if the waterproofing of the battery fails, the electrolyte may leak.

[0003] In recent years, solid electrolyte (SSE) batteries have been developed. Solid electrolytes are used to replace liquid electrolytes in alkali metal or alkaline earth metal ion batteries (such as Li ion) and pure alkali metal or pure alkaline earth metal anode batteries (such as Li metal) because they can solve the safety and leakage issues associated with liquid electrolytes. The disadvantage of solid electrolytes is that it is more difficult to establish a close interface between the electrode and the electrolyte. This can lead to a shorter battery life.

[0004] At the same time, in order to extend the battery life and develop safer batteries, all-solid-state batteries including solvent-free electrodes have been developed. By eliminating NMP (N-methyl-2-pyrrolidone), the most commonly used solvent in the electrode formulation, the total energy consumption in the production process can be reduced by 47%. The presence of solvents requires debinding operations at high temperatures, resulting in energy losses, but these solvents cannot be completely eliminated. The solvents, like NMP, are highly toxic and harmful to health. Water can eliminate solvent recovery costs and solve toxicity issues, but it remains a challenge to produce thick electrodes with high energy density and excellent mechanical strength. Summary of the invention

[0005] The object of the present invention is to overcome the above disadvantages by developing a solvent-free electrode which has excellent mechanical strength and high energy density while being able to form a close interface with a solid electrolyte.

[0006] More specifically, the present invention is to produce a solvent-free electrode comprising an active material (the material is a source or acceptor of lithium ions), a carbon-based material for improving the conductivity of the electrode, and a polymer for binding the active material and the carbon-based material. Advantageously, the electrode consists only of the active material, the carbon-based material and the polymer.

[0007] This new electrode formulation completely eliminates the need for the use of solvents to make the electrodes. This simplifies manufacturing and reduces production costs.

[0008] Combined with a solid electrolyte whose composition is similar to the polymer used as a binder in the electrode, the battery life is extended and the performance is improved due to the intimate interface between the electrode and electrolyte materials.

[0009] More specifically, the present invention relates to a solvent-free electrode for a lithium-ion battery, the electrode comprising:

[0010] - active materials acting as a source of lithium ions, which are able to receive lithium ions and / or release lithium ions into their structure;

[0011] -Carbon-based materials to improve the conductivity of electrodes;

[0012] It is characterized in that it further comprises a polymer having at least a maleimide group, an acrylate group or a methacrylate group, and the polymer acts as a binder between the active material and the carbon-based material.

[0013] According to an alternative embodiment of the invention, the electrode has one or more of the following features:

[0014] - the polymer further comprises a salt of an alkali metal and / or an alkaline earth metal;

[0015] - at least the maleimide group, acrylate group or methacrylate group is a terminal group;

[0016] - the polymer comprises at least one maleimide group and a lithium salt or a sodium salt;

[0017] - The active material comprises LiFePO4, LiNiMnCoO2, LiCoO2, Li4Ti5O 12 or graphite, the carbon-based material comprising activated carbon, carbon black and / or graphite;

[0018] - it contains 50% to 80% by weight, preferably 60% to 75% by weight of active substances, 0.5% to 5% by weight, preferably 1% to 4% by weight of carbon-based materials, and 10% to 45% by weight, preferably 20% to 35% by weight of polymers;

[0019] - said polymer is obtained from a polymerizable composition comprising:

[0020] a first polymer comprising a first part capable of coordinating cations of alkali metals and / or alkaline earth metals and a second part which is photoactivatable and / or thermally activatable;

[0021] Oligomers having at least two photoactivatable and / or thermally activatable groups;

[0022] a second polymer comprising a third moiety comprising a salt of an alkali metal or an alkaline earth metal;

[0023] Plasticizers;

[0024] a polymerization initiator for initiating polymerization between the second part of the first polymer and the photoactivatable and / or thermally activatable groups of the oligomer under the action of a temperature of 20° C. to 150° C. or under the action of radiation;

[0025] one or more of the second moiety and the photoactivatable and / or thermally activatable group is a maleimide group, an acrylate group or a methacrylate group;

[0026] - the polymerizable composition comprises, based on the total weight of the polymerizable composition, 10 to 50 wt% of a first polymer, 1 to 20 wt% of an oligomer, 1 to 20 wt% of a second polymer, 20 to 60 wt% of a plasticizer, and 0.01 to 2 wt% of a polymerization initiator;

[0027] - the polymerizable composition further comprises 0.5% to 5% by weight of an alkali metal salt and / or an alkaline earth metal salt, based on the total weight of the polymerizable composition;

[0028] - The first part of the polymerizable composition comprises polyethylene oxide moieties.

[0029] The term "photoactivatable" as used in this disclosure includes components, molecules, groups or moieties that can be activated by radiation, such as but not limited to ultraviolet (UV) radiation, infrared (IR) radiation, visible radiation or a combination thereof.

[0030] The term "heat-activatable" as used in the present disclosure includes components, molecules, groups or moieties that can be activated by a change in temperature. In particular, the change in temperature is heating. Advantageously, the activation temperature is from 20°C to 150°C, preferably from 25°C to 100°C.

[0031] Activation by heat and / or radiation includes, but is not limited to, activation for oligomerization, polymerization, or cross-linking, and / or activation for initiating oligomerization, polymerization, or cross-linking.

[0032] A "terminal group" is considered to be a group present at one end of a polymer.

[0033] As used in this disclosure, "telechelic oligomer" is considered to be an oligomer capable of subsequent polymerization due to the presence of at least one reactive group at each end of (the chain of) the oligomer.

[0034] A second aspect of the invention relates to a battery comprising a solvent-free electrode as described above for at least one of the two electrodes.

[0035] Advantageously, the battery further comprises a solid electrolyte made of the polymer having at least a maleimide group, an acrylate group or a methacrylate group.

[0036] A third aspect of the present invention relates to a method for manufacturing a solvent-free electrode as described above, the method comprising the following steps:

[0037] - polymerizing the above polymerizable composition to obtain a polymer having at least a maleimide group, an acrylate group or a methacrylate group;

[0038] - mixing the polymer with active material powder and carbon-based material powder;

[0039] -The resulting mixture is hot pressed to form electrodes.

[0040] Advantageously, the polymer is ground to obtain a powder before the mixing step. Alternatively, after the mixing step and before the pressing step, the mixture is ground, preferably under a nitrogen atmosphere.

[0041] Advantageously, pressing is carried out at a temperature of 90 to 150° C., preferably 100 to 140° C., with a pressing force of 5 to 25 kN, preferably 10 to 20 kN, and a pressing time of 1 to 20 minutes, preferably 3 to 10 minutes.

[0042] Advantageously, the pressing is carried out between the sheet acting as separator and the current collector. BRIEF DESCRIPTION OF THE DRAWINGS

[0043] Objects, advantages and features are shown in the accompanying drawings, which illustrate embodiments of the invention in a non-limiting manner:

[0044] - Figure 1 A first portion of the components of a polymerizable composition is shown;

[0045] - Figure 2 A second portion of the components of the polymerizable composition is shown;

[0046] - Figure 3 A first component of a polymerizable composition is shown;

[0047] - Figure 4 A second component of the polymerizable composition is shown;

[0048] - Figure 5 A third component of the polymerizable composition is shown;

[0049] - Figure 6 The battery pack, in particular the components of the battery cells, are shown;

[0050] - Figure 7 shows a solvent-free electrode according to the present invention;

[0051] - Figure 8 The areal capacity of a battery comprising an electrode according to the invention is shown as a function of the number of charge and discharge cycles.

[0052] - Fig. 9 The voltage and current are shown as a function of time for each cycle of a battery including an electrode of the present invention. DETAILED DESCRIPTION

[0053] The present invention relates to a solvent-free electrode. The electrode comprises an active material, a carbon-based material and a polymer as a binder between the active material and the carbon-based material. Preferably, the electrode is composed of the active material, the carbon-based material and the polymer as a binder.

[0054] The active material is a source of lithium ions and is capable of receiving lithium ions and / or releasing lithium ions into its structure. Preferably, the active material is selected from LiFePO4, LiNiMnCoO2, LiCoO2, Li4Ti5O 12 and graphite. For the cathode, the active material is a source of lithium ions and is therefore responsible for the capacity of the electrode and is able to accept lithium ions in its structure. For the anode, the active material is able to accept and release lithium ions into its structure by insertion. For the cathode, the active material is more specifically LiFePO4, LiNiMnCoO2 or LiCoO2, and for the anode, more specifically Li4Ti5O 12 Or graphite.

[0055] The purpose of the carbon-based material is to increase the conductivity of the electrode. Preferably, it comprises or consists of activated carbon, carbon black and / or graphite.

[0056] The adhesive polymer comprises at least a maleimide group, an acrylate group or a methacrylate group. Preferably, the maleimide group, the acrylate group or the methacrylate group is an end group. Preferably, there are two maleimide groups, the acrylate group or the methacrylate group, one group at each end. Preferably, there is at least one maleimide group.

[0057] Preferably, the polymer further comprises a salt of an alkali metal and / or an alkaline earth metal. Preferably, the salt is a lithium salt or a sodium salt. More preferably, the salt is a lithium salt. Preferably, the polymer comprises at least a maleimide group and a lithium salt or a sodium salt, more preferably a lithium salt.

[0058] The electrode comprises 50% to 80% by weight, preferably 60% to 75% by weight of active material, 0.5% to 5% by weight, preferably 1% to 4% by weight of carbon-based material, and 10% to 45% by weight, preferably 20% to 35% by weight of polymer.

[0059] The polymer is obtained from a polymerizable composition comprising:

[0060] a first polymer comprising a first part capable of coordinating cations of alkali metals and / or alkaline earth metals and a second part which is photoactivatable and / or thermally activatable;

[0061] - an oligomer having at least two photoactivatable and / or thermally activatable groups;

[0062] - a second polymer comprising a third part comprising a salt of an alkali metal or an alkaline earth metal;

[0063] - plasticizers;

[0064] a polymerization initiator for initiating polymerization between the second part of the first polymer and the photoactivatable and / or thermally activatable groups of the oligomer under the action of a temperature of 20° C. to 150° C. or under the action of radiation;

[0065] - one or more of the second moiety and the photoactivatable and / or thermally activatable group is a maleimide group, an acrylate group or a methacrylate group.

[0066] The first part of the first polymer of the polymerizable composition of the present invention is capable of coordinating cations of alkali metals and / or alkaline earth metals, advantageously coordinating cations of alkali metals and / or alkaline earth metals in the electrode of the present invention. In other words, the first part is advantageously selected to ensure ionic conductivity within the electrode. Non-limiting examples of the first part are Figure 1 Advantageously, in Figure 1 In the above, u represents the number of repetitions and is selected from 20 to 80, preferably 30 to 70, more preferably 40 to 60, for example 50 to 55.

[0067] The second part of the first polymer of the polymerizable composition of the present invention is a part that allows the polymerizable composition to polymerize. Therefore, the second part is photoactivatable and / or thermally activatable. Non-limiting examples are maleimide parts (such as Figure 2 ), an acrylate portion and a methacrylate portion.

[0068] Advantageously, the first polymer has a molar mass of 1000 to 5000 g / mol, preferably 1500 to 4000 g / mol, for example 2000 to 3000 g / mol, more preferably 2250 to 2750 g / mol, for example 2350 to 2600 g / mol.

[0069] Advantageously, the first polymer comprises from 0.1 to 0.7 mEq (milliequivalent) of the second moiety per gram of first polymer, preferably from 0.2 to 0.6 mEq, more preferably from 0.3 to 0.5 mEq, for example from 0.35 to 0.45 mEq, or 0.4 mEq.

[0070] A specific example of the first polymer is α-methoxyω-maleimide polyethylene oxide, such as Figure 3 As shown, polyethylene glycol methacrylate (PEGMA) and α-methoxyω-maleimide polyethylene glycol.

[0071] Advantageously, the polymerizable composition contains 10 to 50 wt. %, preferably 12 to 45 wt. %, for example 15 to 40 wt. % of the first polymer, based on the total weight of the polymerizable composition.

[0072] The polymerizable composition also includes an oligomer. The oligomer has at least two photoactivatable and / or heat-activatable groups. These groups can polymerize with the second part of the first polymer and / or the third part of the second polymer. Preferably, the groups of the oligomer can polymerize with at least the third part of the second polymer. The photoactivatable and / or heat-activatable groups can be, but are not limited to, maleimide groups, acrylate groups, and methacrylate groups.

[0073] Advantageously, the oligomer comprises from 0.1 to 0.7 mEq (milliequivalents) of photoactivatable groups and / or thermally activatable groups per gram of oligomer, preferably from 0.2 to 0.9 mEq, more preferably from 0.3 to 0.8 mEq, for example from 0.4 to 0.7 mEq, or from 0.5 to 0.6 mEq.

[0074] Examples of oligomers are Figure 4 The PPG-block-PEG-block-PPG shown, α, ω-bis(maleimide), is a polyethylene oxide-polypropylene oxide (PEO-PPO) having a maleimide group at each end of the chain. Advantageously, x+z is 2 to 20, preferably 5 to 15, more preferably 6 to 12, for example 8 to 9. Advantageously, y is 20 to 100, preferably 40 to 80, more preferably 50 to 75, for example 60 to 70, or 62 to 67.

[0075] Another example of an oligomer is polyethylene glycol (PEG) with a methacrylate group (MA) at each end of the chain (PEG-DiMA).

[0076] Advantageously, the oligomer has a molar mass of 250 to 10,000 g / mol, preferably 500 to 5,000 g / mol, more preferably 750 to 4,000 g / mol, for example 1,000 to 3,750 g / mol, or 2,000 to 3,600 g / mol.

[0077] Advantageously, the polymerizable composition contains 1 to 20 wt. %, preferably 2 to 15 wt. %, for example 3 to 15 wt. % of the oligomer, based on the total weight of the polymerizable composition.

[0078] Advantageously, the oligomer comprises at least one photoactivatable and / or thermally activatable group at each end of the oligomer chain, in which case the oligomer is a telechelic oligomer. By adding a telechelic oligomer to the polymerizable composition, it is possible to better control the polymerization and thus the structure of the resulting polymer network. Advantageously, the polymer network is a linear polymer network. Furthermore, the chain between two nodes of the polymeric composition obtained in this way is long enough to make the polymeric composition rather "loose" and to provide the electrode with excellent ionic conductivity.

[0079] Advantageously, the oligomer can act as a plasticizer and / or amplifier of the ionic conductivity of the electrode.

[0080] The second polymer of the polymerizable composition contains a third part. Advantageously, the third part comprises an alkali metal salt and / or an alkaline earth metal salt. Advantageously, the alkali metal comprises lithium, sodium, potassium or a combination thereof. Preferably, the alkali metal is lithium. Advantageously, the alkaline earth metal comprises magnesium, beryllium, calcium or a combination thereof. Preferably, the alkaline earth metal is magnesium.

[0081] Advantageously, the third part can supply alkali metal and / or alkaline earth metal cations into the electrode. Advantageously, alkali metal and / or alkaline earth metal cations can move along the first polymer and oligomer in the electrode. This movement affects the ionic conductivity of the electrode. In addition, the third part that is integrated into the second polymer chain also makes it possible to reduce the mobility of the counter anion of alkali metal and / or alkaline earth metal in the electrode, which makes it possible to increase the mobility of alkali metal and / or alkaline earth metal.

[0082] Figure 5 An example of the second polymer of the polymerizable composition of the present invention is shown, wherein the third moiety is lithium bis(trifluoromethane)sulfonyl imide (LiSTFSI, CAS No. 210226-98-5).

[0083] Advantageously, the polymerizable composition contains 1 to 20 wt. %, preferably 2 to 15 wt. %, such as 5 to 10 wt. % of the second polymer, based on the total weight of the polymerizable composition.

[0084] Plasticizers in the polymerizable composition advantageously allow the components of the composition to be solubilized. Examples of plasticizers include, but are not limited to, propylene carbonate.

[0085] Advantageously, the polymerizable composition contains 20% to 60% by weight, preferably 25% to 55% by weight, for example 30% to 50% by weight, of plasticizer, based on the total weight of the polymerizable composition.

[0086] The composition also comprises a polymerization initiator. The polymerization initiator enables the initiation of polymerization between the second part of the first polymer, the photoactivatable and / or thermally activatable groups of the oligomer and the third part of the second polymer. The initiation of polymerization and / or the polymerization itself is carried out at a temperature of 20° C. to 200° C., preferably 20° C. to 150° C., more preferably 25° C. to 100° C., for example 30° C. to 80° C., or under the action of radiation. Advantageously, the radiation comprises one or more of: UV radiation, IR radiation and visible radiation (VIS).

[0087] If the polymerization step is carried out under the action of radiation, preferably UV radiation, its duration is from 5 seconds to 20 minutes, for example from 10 seconds to 15 minutes, preferably from 20 seconds to 10 minutes, more preferably from 30 seconds to 5 minutes, for example 4 minutes, 3 minutes, 2 minutes, 1 minute, or 55 seconds, 50 seconds or 45 seconds.

[0088] If the polymerization is carried out under the action of temperature, it lasts from 1 minute to 5 hours, preferably from 5 minutes to 4 hours, for example from 10 minutes to 3 hours, from 20 minutes to 2.5 hours, or from 30 minutes to 2 hours.

[0089] Advantageously, the polymerization initiator is free radical in nature. In the present disclosure, this means that the polymerization initiator is capable of releasing free radicals under the action of temperature or radiation as described above. These free radicals then initiate polymerization between the first polymer, the second polymer and the oligomer of the composition.

[0090] Examples of the polymerization initiator include, but are not limited to, 2,2'-azobis(isobutyronitrile) (AIBN) and 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone (CAS No. 106797-53-9).

[0091] Advantageously, the polymerizable composition contains 0.01 to 2 wt. %, preferably 0.1 to 1.5 wt. %, for example 0.25 to 1 wt. % of polymerization initiator, based on the total weight of the polymerizable composition.

[0092] The polymerizable composition may also include an alkali metal salt and / or an alkaline earth metal salt. Advantageously, the alkali metal salt includes or consists essentially of a lithium salt. Advantageously, the alkaline earth metal salt includes or consists essentially of a magnesium salt. Non-limiting examples of salts include lithium bis(fluorosulfonyl)imide (LIFSI) and lithium bis(trifluoromethanesulfonyl)imide (LITFSI).

[0093] The inventors surprisingly found that by adding an alkali metal salt and / or an alkaline earth metal salt to a polymerizable composition, an electrode has improved ionic conductivity compared to an electrode made with a polymer obtained from a composition without the addition of an alkali metal salt and / or an alkaline earth metal salt. The inventors believe that the improved conductivity is achieved through a synergistic effect between the salt of the third part of the second polymer and the separate salt added to the composition.

[0094] Advantageously, if the polymerizable composition comprises an alkali metal salt and / or an alkaline earth metal salt, the composition contains 0.5 to 5 wt%, preferably 0.75 to 4 wt%, for example 1 to 3 wt% of the salt, based on the total weight of the polymerizable composition.

[0095] According to the present disclosure, a polymer that acts as a binder between an active material and a carbon-based material is obtained by polymerizing a polymerizable composition. Using the polymer obtained from the polymerization of the polymerizable composition, an electrode is manufactured by extrusion or hot pressing. The hot pressing manufacturing method ( Figure 7 ). The method comprises the following steps:

[0096] - polymerizing the above polymerizable composition to obtain a polymer having at least a maleimide group, an acrylate group or a methacrylate group;

[0097] - mixing the polymer with the active material powder and the carbon-based material powder;

[0098] The resulting mixture 11 is hot pressed to produce electrodes 2 , 3 .

[0099] Advantageously, the polymer is ground before being mixed with the other powders. Alternatively, a mixture comprising the polymer and the other two powders is ground before polymerization.

[0100] Advantageously, the method comprises an additional step of freezing the polymer or the mixture before the grinding step, in order to render the polymer brittle, this step being carried out for example under a nitrogen atmosphere.

[0101] The pressing is carried out at a temperature of 90 to 150° C., preferably 100 to 140° C., a pressing force of 5 to 25 kN, preferably 10 to 20 kN, and a pressing time of 1 to 20 minutes, preferably 3 to 10 minutes.

[0102] Advantageously, the pressing is performed between the sheet 9 and the current collector 10. The sheet can be an integral part of the resulting electrode, or can be removed, even falling off on its own, while retaining a functional electrode. For example, the sheet can be a cellulose sheet used as a separator, and the current collector can be made of aluminum or an aluminum alloy.

[0103] The present disclosure also relates to a battery comprising the solvent-free electrode of the present invention. Figure 6 An example of a battery 1 is shown. It has a button cell configuration, known in the art as a CR2032 type configuration.

[0104] The battery 1 comprises an anode 2 and a cathode 3, wherein at least one of the two electrodes is made of a formulation according to the invention. Advantageously, the battery 1 also comprises, between the anode 2 and the cathode 3, a solid polymer electrolyte 4 made of the polymerizable composition described above.

[0105] Advantageously, the battery 1 further comprises a button cell cover 5, a button cell base 6, a gasket 7 and a spring 8. The gasket 7 and the spring 8 ensure good contact between the other components 2, 3, 4, 5, 6 of the battery 1.

[0106] The performance of a battery was tested, the battery comprising a cathode according to the invention comprising 70% by weight of LiFePO4 as active material, 28% by weight of a polymer containing maleimide groups, 2% by weight of carbon black. The cathode was prepared by mixing the different powders and pressing them between a cellulose sheet and an aluminum current collector at a pressure of 15 kN at a temperature of 120° C. for 5 minutes.

[0107] The cathode was assembled in a battery pack comprising a commercial Li4Ti5O 12 (LTO) anode, theoretical capacity is 1.25 mAh / cm 3 , and includes standard liquid electrolyte (LP30).

[0108] The battery life was tested by charging and discharging the battery between 1.5V and 2.4V for more than 30 cycles, as shown in Fig. 9 This is the first ten cycles. The cycle rate relative to LTO is C / 16, which is equivalent to a charge of 0.140mA. Charging is done by applying a constant current and discharging is done by applying the same but negative current. During each cycle, the battery is charged to 100% state of charge and discharged to 100% depth of discharge.

[0109] Figure 8 Results for two samples are shown, with the figure plotting the areal capacity as a function of cycle number. Figure 8It shows that the areal capacity loss after 30 cycles is less than 25% compared with the areal capacity of the first cycle, and the capacity stabilizes after about 15 cycles. Therefore, the battery pack has good capacity stability, which means a long service life.

Claims

1. A solvent-free electrode (2, 3) for a lithium-ion battery, the electrode comprising: - active materials acting as a source of lithium ions, which are able to receive lithium ions and / or release lithium ions into their structure; A carbon-based material to improve the conductivity of the electrodes (2, 3); Features It also contains a polymer having at least a maleimide group, an acrylate group or a methacrylate group, which serves as a binder between the active material and the carbon-based material.

2. The solvent-free electrode (2, 3) according to claim 1, characterized in that The polymer may also contain a salt of an alkali metal and / or an alkaline earth metal.

3. The solvent-free electrode (2, 3) according to claim 1 or 2, characterized in that: The at least maleimide group, acrylate group or methacrylate group is a terminal group.

4. The solvent-free electrode (2, 3) according to claim 2, characterized in that The polymer comprises at least one maleimide group and a lithium salt or a sodium salt.

5. The solvent-free electrode (2, 3) according to claim 1 or 2, characterized in that: The active material includes LiFePO4, LiNiMnCoO2, LiCoO2, Li4Ti5O12 or graphite, and the carbon-based material includes activated carbon, carbon black and / or graphite.

6. The solvent-free electrode (2, 3) according to claim 1 or 2, characterized in that: It contains 50 to 80 weight percent of active material, 0.5 to 5 weight percent of carbon-based material, and 10 to 45 weight percent of polymer.

7. The solvent-free electrode (2, 3) according to claim 1 or 2, characterized in that: It contains 60 to 75 weight percent of active material, 1 to 4 weight percent of carbon-based material, and 20 to 35 weight percent of polymer.

8. The solvent-free electrode (2, 3) according to claim 1 or 2, characterized in that: The polymer is obtained from a polymerizable composition comprising: a first polymer comprising a first part capable of coordinating cations of alkali metals and / or alkaline earth metals and a second part which is photoactivatable and / or thermally activatable; - an oligomer having at least two photoactivatable and / or thermally activatable groups; - a second polymer comprising a third part comprising a salt of an alkali metal or an alkaline earth metal; - plasticizers; a polymerization initiator for initiating polymerization between the second part of the first polymer and the photoactivatable and / or thermally activatable groups of the oligomer under the action of a temperature of 20° C. to 150° C. or under the action of radiation; - one or more of the second moiety and the photoactivatable and / or thermally activatable group is a maleimide group, an acrylate group or a methacrylate group.

9. The solvent-free electrode (2, 3) according to claim 8, characterized in that The polymerizable composition comprises 10 to 50 wt % of a first polymer, 1 to 20 wt % of an oligomer, 1 to 20 wt % of a second polymer, 20 to 60 wt % of a plasticizer, and 0.01 to 2 wt % of a polymerization initiator, based on the total weight of the polymerizable composition.

10. The solvent-free electrode (2, 3) according to claim 8, characterized in that The polymerizable composition further comprises 0.5 wt % to 5 wt % of an alkali metal salt and / or an alkaline earth metal salt, based on the total weight of the polymerizable composition.

11. The solvent-free electrode (2, 3) according to claim 8, characterized in that The first part of the polymerizable composition comprises a polyethylene oxide moiety.

12. A cell (1) comprising a solvent-free electrode (2, 3) according to any one of the preceding claims for at least one of the two electrodes (2, 3).

13. The battery (1) according to claim 12, further comprising a solid electrolyte made of the polymer having at least a maleimide group, an acrylate group or a methacrylate group.

14. A method for manufacturing a solvent-free electrode (2, 3) according to any one of claims 1 to 11, the method comprising the following steps: - polymerizing the polymerizable composition according to one of claims 8 to 11 to obtain a polymer having at least maleimide groups, acrylate groups or methacrylate groups; - mixing the polymer with the active material powder and the carbon-based material powder; - The resulting mixture (11) is hot pressed to produce electrodes (2, 3).

15. The method for manufacturing a solvent-free electrode (2, 3) according to claim 14, characterized in that: The pressing is performed at a temperature of 90° C. to 150° C., a pressing force of 5 kN to 25 kN, and a pressing time of 1 minute to 20 minutes.

16. The method for manufacturing a solvent-free electrode (2, 3) according to claim 14, characterized in that: The pressing is performed at a temperature of 100° C. to 140° C., a pressing force of 10 kN to 20 kN, and a pressing time of 3 minutes to 10 minutes.

17. The method for manufacturing a solvent-free electrode (2, 3) according to claim 14 or 15, characterized in that The mixture (11) is pressed between the sheet (9) and the current collector (10).

18. The method for manufacturing a solvent-free electrode (2, 3) according to claim 14 or 15, characterized in that: The polymer is ground either before the mixing step or after the mixing step.